Application of Aptamers in Virus Detection and Antiviral Therapy - Zou, Xinran; Wu, Jing; Gu, Jiaqi; Shen, Li; Mao, Lingxiang (Frontiers in Microbiology, 2019)
Viral infection is a serious health problem for human beings and animals. Accurate and early detection of viruses is often crucial to improve clinical diagnosis anddirect therapy . Aptamers are mostly single-stranded nucleotide sequences that are artificially synthesized by an in vitro technology known as the Systematic Evolution of Ligands by Exponential Enrichment (SELEX). Similar to antibodies, aptamers bind specifically to their targets. However, compared with antibody, aptamers are easy to synthesize and modify, andthey have broad targets . Thus, aptamers are promising for viral detection and therapy. In this review, we briefly introduce aptamer-based biosensors (aptasensors) and describe their applications in rapid detection of viruses and as antiviral agents in treating infections. We summarize available data about the use of aptamers to detect and inhibit viruses. Furthermore, for the first time, we list aptamers specific to different viruses that have not yet been studied in viral detection or treatment. Finally, we analyze barriers and developing perspectives in the application of aptamer-based viral detection and therapeutics.